Granivore impact on soil-seed reserves in the central Monte desert, Argentina - Marone, L. (1998)
1. Mechanisms of grass- and forb-seed input and output in the central Monte desert of Argentina were studied in 1995 to test the hypothesis that seed consumption by autumn-winter granivores, especially birds, has qualitative as well as quantitative effects on soil-seed reserves. 2. The abundance of perennial grass seeds in late summer soils (≃ 2400 seeds m-2 or 0.36 g m-2) remained unchanged the following early spring (≃ 2700 seeds m-2 or 0.39 g m-2), despite the incorporation of about 3000 seeds m-2 or 0.71 g m-2 newly produced grass seeds during autumn-winter. Grass seeds appeared to be heavily consumed, especially the medium-sized ones. 3. The annual forb-seed bank was about the same size in late summer (≃ 5500 seeds m-2 or 1.34 g m-2) as in early spring (≃ 6500 seeds m-2 or 1.53 g m-2). Since forb-seed production had been relatively low (≃ 400 seeds m-2 or 0.12 g m-2), these seeds apparently suffered negligible postdispersal losses. 4. This pattern of grass- and forb-seed loss coincides with the pattern of seed consumption by granivorous birds - on average, 93% of seed mass in bird stomachs was from grass seeds, while only 7% was from forb seeds. 5, Further evidence of a major impact of bird foraging on seed reserves is that the mass of particular grass seeds that was lost from soils was positively correlated with the mass of such seeds in bird diets, and that the main target of bird consumption, i.e. medium-sized grass seeds, suffered the highest postdispersal loss. 6. It is concluded that autumn-winter granivores in the central Monte desert, particularly birds, mainly consume newly produced grass seeds and that they might have major qualitative as well as quantitative impacts on soil-seed reserves.